2008
DOI: 10.1146/annurev.publhealth.29.020907.090843
|View full text |Cite
|
Sign up to set email alerts
|

Heat Stress and Public Health: A Critical Review

Abstract: Heat is an environmental and occupational hazard. The prevention of deaths in the community caused by extreme high temperatures (heat waves) is now an issue of public health concern. The risk of heat-related mortality increases with natural aging, but persons with particular social and/or physical vulnerability are also at risk. Important differences in vulnerability exist between populations, depending on climate, culture, infrastructure (housing), and other factors. Public health measures include health prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
888
3
20

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,445 publications
(993 citation statements)
references
References 73 publications
13
888
3
20
Order By: Relevance
“…Some people are less able to cope with heat stress than others. A wide range of chronic diseases and medical treatments, social isolation and some types of occupation increase the risk of heat stress in individuals (4,5). Across Europe, housing and socio-economic conditions showed varying influence on the impacts of heat on health in the populations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some people are less able to cope with heat stress than others. A wide range of chronic diseases and medical treatments, social isolation and some types of occupation increase the risk of heat stress in individuals (4,5). Across Europe, housing and socio-economic conditions showed varying influence on the impacts of heat on health in the populations.…”
Section: Introductionmentioning
confidence: 99%
“…Although case-control studies have identified socially isolated individuals who live alone as being at very high risk of heatwave mortality, it could not be assessed ( ) whether deaths at home were mostly occurring among people who live alone. In France, mortality in retirement homes increased by 00% during the more extreme August 00 heatwave ( 4). Similarly, mortality in nursing homes in northern Italy increased by 50%, and increases in heat-related morbidity as well as failures in care were reported ( 5).…”
Section: Introductionmentioning
confidence: 99%
“…En primer lugar, un clima más cálido y una mayor frecuencia de olas de calor se traducirán en una mayor mortalidad y morbilidad (Kovats y Hajat, 2008). Los episodios de calor extremo representan una amenaza seria para las poblaciones de las ciudades, así como un reto para la salud pública.…”
Section: Los Retos En La Adaptación Al Cambio Climático En Entornos Uunclassified
“…Vulnerability assessments, public health researchers agree, are a key part of planning to enhance adaptation and response to extreme weather events; they also agree that identifying vulnerable subpopulations remains a key issue in plan development. [7][8][9][10][11][12][13] Such vulnerable populations include the elderly, who are more physiologically susceptible, and the poor, who have fewer resources to prepare for and cope with extreme weather events. 14 Indeed, some suggested vulnerability assessment strategies use a local-level approach (that is, a bottom-up, rather than top-down, planning system), which in turn informs adaptation strategies and may build resilience at multiple community levels through early anticipation and response to problems.…”
Section: Introductionmentioning
confidence: 99%